2020
DOI: 10.1111/brv.12578
|View full text |Cite
|
Sign up to set email alerts
|

Development and evolution of the tetrapod skull–neck boundary

Abstract: The origin and evolution of the vertebrate skull have been topics of intense study for more than two centuries. Whereas early theories of skull origin, such as the influential vertebral theory, have been largely refuted with respect to the anterior (pre-otic) region of the skull, the posterior (post-otic) region is known to be derived from the anteriormost paraxial segments, i.e. the somites. Here we review the morphology and development of the occiput in both living and extinct tetrapods, taking into account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(38 citation statements)
references
References 104 publications
2
36
0
Order By: Relevance
“…In gnathostomes, the most anterior somites contribute to the occipital bones [ 67 – 69 ]. The sclerotome from these occipital somites contributes to the basioccipital and exoccipital [ 70 – 72 ], so the occipital phenotypes observed in zebrafish and mouse Nkx3 .…”
Section: Discussionmentioning
confidence: 99%
“…In gnathostomes, the most anterior somites contribute to the occipital bones [ 67 – 69 ]. The sclerotome from these occipital somites contributes to the basioccipital and exoccipital [ 70 – 72 ], so the occipital phenotypes observed in zebrafish and mouse Nkx3 .…”
Section: Discussionmentioning
confidence: 99%
“…In gnathostomes, the most anterior somites contribute to the occipital bones (Ferguson and Graham, 2004;Maddin et al, 2020;Morin-Kensicki et al, 2002). The sclerotome from these occipital somites contributes to the basioccipital and exoccipital (Couly et al, 1993;O'Rahilly, 2003, 1994), so the occipital phenotypes observed in zebrafish and mouse nkx3.2/Nkx3.2 mutants are consistent with the role of Nkx3.2 in the sclerotome.…”
Section: Discussionmentioning
confidence: 99%
“…The number of somites that are incorporated into the occiput of the skull has been the subject of study for a long time up until today (e.g., Platt, 1897;Hunter, 1935;de Beer, 1937;Couly et al, 1993;Burke et al, 1995;Kuratani et al, 1999;Handrigan and Wassersug, 2007;Kuratani and Ota, 2008;Maddin et al, 2020). Early research using traditional techniques of histology and whole-mount embryology showed that agnathans (the jawless fishes) do not incorporate any somites into the head (Kuratani et al, 1999), whereas gnathostomes (jawed fishes plus tetrapods) do, and recruit a variable number of somites to form the bones of the occiput (de Beer, 1937).…”
Section: List Of Appendicesmentioning
confidence: 99%
“…One potential osteological correlate has been proposed for such investigations: foramina pertaining to the posterior-most cranial nerve, cranial nerve twelve (n.XII; Maddin et al, 2020), which is also generally referred to as the hypoglossal nerve or hypoglossal nerve complex in amniotes (de Beer, 1937;Romer and Edinger, 1942;Romer and Parsons, 1977;Grande and Bemis, 1998). As the most posteriorly situated cranial nerve, the hypoglossal nerve marks the boundary between cranial and spinal nerves (Barnard, 1940;Noden, 1983;Couly et al, 1993;Ferguson and Graham, 2004;Yaryhin and Werneburg, 2018).…”
Section: 2: Occiput and Braincase Morphologymentioning
confidence: 99%
See 1 more Smart Citation